Taxanes alone or in combination with anthracyclines as first-line therapy of patients with metastatic breast cancer - (:unkn) unknown (AMER SOC CLINICAL ONCOLOGY, 2008)
Purpose Taxanes (paclitaxel or docetaxel) have been sequenced or combined with anthracyclines (doxorubicin or epirubicin) for the first-line treatment of advanced breast cancer. This meta-analysis uses data from all relevant trials to detect any advantages of taxanes in terms of tumor response, progression-free survival (PFS), and survival. Patients and Methods Individual patient data were collected on eight randomized combination trials comparing anthracyclines + taxanes (+ cyclophosphamide in one trial) with anthracyclines + cyclophosphamide (+ fluorouracil in four trials), and on three single-agent trials comparing taxanes with anthracyclines. Combination trials included 3,034 patients; single-agent trials included 919 patients. Results Median follow-up of living patients was 43 months, median survival was 19.3 months, and median PFS was 7.1 months. In single-agent trials, response rates were similar in the taxanes (38%) and in the anthracyclines (33%) arms (P =.08). The hazard ratios for taxanes compared with anthracyclines were 1.19 (95% CI, 1.04 to 1.36; P =.011) for PFS and 1.01 (95% CI, 0.88 to 1.16; P = .90) for survival. In combination trials, response rates were 57% (10% complete) in taxane-based combinations and 46% (6% complete) in control arms (P <.001). The hazard ratios for taxane-based combinations compared with control arms were 0.92 (95% CI, 0.85 to 0.99; P = .031) for PFS and 0.95 (95% CI, 0.88 to 1.03; P = .24) for survival. Conclusion Taxanes were significantly worse than single-agent anthracyclines in terms of PFS, but not in terms of response rates or survival. Taxane-based combinations were significantly better than anthracycline-based combinations in terms of response rates and PFS, but not in terms of survival.
Keywords: PHASE-III TRIAL; EUROPEAN ORGANIZATION; DOXORUBICIN; CYCLOPHOSPHAMIDE; CHEMOTHERAPY; PACLITAXEL; MULTICENTER; DOCETAXEL; FLUOROURACIL